Disposal practice and factors associated with unused medicines in Malaysia: a cross-sectional study - Leong Seng Wang; Zoriah Aziz; Zamri Chik (BMC, 2021)
Abstract Background The improper disposal of unused medicines is a worldwide concern because of its impact on the environment, economy, and health. This study aims to describe the disposal practice of unused medicine and identify factors associated with unused medicines in Malaysia. Methods This was a cross-sectional, face to face interview-based survey using a structured questionnaire. We used a convenience sampling method to recruit participants from Kuala Lumpur and Selangor in Malaysia. Results We interviewed 1184 participants, and the response rate was 96%. Out of the total respondents, 995 (84%) reported having unused medicines. About a quarter of respondents kept unused medicines in the cabinet, and another quarter disposed of them into the trash or toilet. Only half of the respondent who used medicines for chronic illnesses had unused medicines compared to about 90% of respondents who used medicines for acute illnesses. The main reason for having unused medicines among those who used medicines for chronic illness was non-adherence (69%, p <  0.05). Only 27% of these respondents returned unused medicines under the "Medicine Return Programme (MRP)". The other group who used medicines for acute illnesses had unused medicines because their health conditions improved. Thus, most of the unused medicines will eventually end up in household waste. A multivariate logistic regression analysis identified respondents who used medicines for acute illnesses as the strongest predictor of having unused medicines (Odds Ratio (OR) = 29.8; p <  0.001), followed by those who pay for their medicines (OR = 6.0; p < 0.001) and those who were willing to participate the Medicine Return Programme (OR = 2.5; p = 0.009). Conclusion The prevalence of unused medicines and their improper disposal were high in Malaysia. Unused medicines are associated with people who use medicines for acute illnesses, pay for their medication, and are willing to participate in an MRP. Rationale prescription and optimal dispensing practice, together with a broader MRP facilities coverage, could reduce unused medicine possession.